STATUS KELEMBAGAAN KELOMPOK MASYARAKAT PENGAWAS BIDANG PERIKANAN DI NEGERI HUKURILA KECAMATAN LEITIMUR SELATAN KOTA AMBON - Talakua, Eygner Gerald; Lopulalan, Yoisye; Likipiouw, Geral Ignatius (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
One of the Fisheries Supervisory Community Groups in Ambon City is the "Tihulessy" Community Supervisory Group in Hukurila Village, South Leitimur District. The fisheries supervisory community group has carried out its duties/obligations for 2 years, but there is a main obstacle, namely that there are no adequate monitoring facilities and infrastructure so that monitoring activities are limited to the nearest sea and coastal areas. For this reason, an evaluation of the level of institutional development of fisheries supervisory community groups needs to be carried out, so this research aims to analyze the level of development and determine priorities for institutional development of fisheries supervisory community groups in Hukurila State. Primary data obtained through structured interviews using a questionnaire with 10 respondents was then analyzed qualitatively using an institutional development framework approach. The research results show that the institutional status is low or does not have sufficient institutional resources to ensure its continuity. Institutional development priorities are divided into: 1). The short-term priority scale is increasing the quality and quantity of roles, namely the task of monitoring fisheries resources; 2). The medium-term priority scale is organizational development, improving leadership, improving management systems, building relationships/communication/and coordination, budget management, and procurement of work support facilities and tools; and 3). The long-term priority scale is increasing skills and developing members, as well as developing products or the economic value of fisheries resources in Hukurila Village.